Finite element analysis of magnetic flux leakage detection: Characterizing defect size and depth effects - Wang Jie; Mohd. Kamal Mohd. Shah; Choong Wai Heng; Nahiyan Al-Azad (Global Academic Excellence, 2024)
The analysis and identification of defect signals in magnetic flux leakage (MFL) inspection are crucial aspects of MFL detection technology. To investigate the impact of defect size and depth on magnetic flux density in steel pipes, this paper creates 100 finite element models of MFL detection for defects with lengths and depths ranging from 1 to 10 mm. Simulation results show that the radial component of the magnetic flux leakage field exhibits two peaks near the defect edges, while the axial component has a peak at the defect center. As the defect size increases, the peak-to-peak distance of the radial component increases, while its peak value decreases; the peak value of the axial component increases with defect length within a certain range. These findings enhance the understanding of MFL detection and its relationship with defect size and depth, providing insights that can inform the development of more accurate and efficient detection techniques.